Physico-chemical and sensory characteristics of dumpling crackers with the addition of tilapia bone flour - Intan Nurzahra Kaswanto (Universitas Djuanda, 2019)
This study was aimed to determine the physico-chemical, sensory characteristics, and the best treatment of dumpling crackers added by tilapia bone flour. The treatment given consisted of P0 (without addition), P1 (5% tilapia bone flour), P2 (10% tilapia bone flour), and P3 (15% tilapia bone flour). Analysis parameters observed were physical characteristics (volume expands and hardness), chemical (proximate, calcium, phosphorus), and sensory. The results showed that addition of tilapia bone flour 10% (P2) produced the best dumpling crackers with physical characteristics were volume expands of 83.58% and hardness of 1.28 N. Chemical characteristics (proximate) of water, ash, protein, fat, and carbohydrate content were 2.32, 4.62, 7.68, 27.35, and 60.34% respectively. The dumpling crackers (P2) contained calcium 1.21 and phosphorus 0.66%. The sensory characteristics of P2 raw dumpling crackers were brightly unevenly colored, less chewy, and slightly fish-scented while the fried dumpling crackers were yellowish creamy, crunchy, slightly fish-scented, and savory.